Cultural Integration in Mathematics Learning: A Systematic Literature Review of the Ethnomathematics Approach (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The integration of culture into mathematics education has become an innovative approach that increasingly attracts researchers and practitioners. Ethnomathematics, defined as the study of relationships between cultural practices and mathematical activities, provides a foundation for contextualized, meaningful, and relevant mathematics instruction. This approach not only facilitates students’ conceptual understanding but also encourages appreciation of local cultural values. In Indonesia, such integration aligns with the Merdeka Belajar curriculum, which emphasizes differentiation, inclusivity, and the development of the Profil Pelajar Pancasila. This study systematically reviews research on cultural integration in mathematics learning through the lens of ethnomathematics pedagogy, while mapping trends, contributions, and challenges. The method employed is a Systematic Literature Review (SLR) following PRISMA guidelines. Articles were collected from international databases (Scopus, ERIC, DOAJ) and national sources (Google Scholar, Garuda), covering publications from 2010 to 2024. A structured selection process was conducted through identification, screening, eligibility assessment, and synthesis. From 162 initial articles, 24 met the inclusion criteria and were analyzed in depth. Data were examined with respect to cultural contexts, pedagogical strategies, and theoretical as well as practical implications. The findings highlight three main contributions. First, in the cognitive domain, students showed improved conceptual understanding and problem-solving skills when mathematics was embedded in cultural contexts. Second, from an affective perspective, ethnomathematics fostered motivation, positive attitudes, and interest in learning. Third, in the socio-cultural domain, this approach strengthened students’ cultural identity and helped preserve local knowledge in formal education. Challenges remain, including limited reference materials, insufficient teacher competence, and lack of explicit curricular support. In conclusion, integrating culture into mathematics education through ethnomathematics not only enhances academic outcomes but also promotes character development and cultural sustainability. The study emphasizes the need for further applied research, development of culturally responsive resources, and teacher training to support sustainable implementation.